MAKNA PENDIDIKAN BAGI KELUARGA IMIGRAN DI PEKANBARU - Tri Astuti; Mita Rosaliza (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Refugees from abroad are foreigners who are in the territory of the unitary state of the Republic of Indonesia due to reasonable fear of persecution for reasons of race, ethnicity, religion, nationality, membership of certain social groups and different political opinions and do not want protection from their home country and have get asylum seeker or refugee status from the United Nations through the high commissioner of refugee affairs in Indonesia. The nature of education is to foster the existence of learners who are socialized, cultured, in a life order that has local, national and global dimensions. This research was carried out in the street Teuku Cik Ditiro Village office Pekanbaru City Pekanbaru. The purpose of this research is find out The Meaning Of Education For Immigrant Families In Pekanbaru. Immigrant society is a group of people who move from one country to another with or without permission from the country of origin or from the destination country. In this case immigrant communities do not get full right about education. Immigrant children do not get a diploma after graduating from school unlike children who study in general. The author uses qualitative methods and uses Purposive Sampling techniques, the data instruments are observation, interviews, questionnairses and documentation. This research suggest that immigrant families have great expectations for the future of their children. With education immigrant families want their children to be successful in the future. Keywords: Imigrant Family,Socioeconomic Condition, Education.